Metamorphosis of Public Speaking Anxiety: Student Fear Transformation Throughout the Introductory Communication Course. Issue 1 (1st January 2020) - LeFebvre, Luke; LeFebvre, Leah E.; Allen, Mike; Buckner, Marjorie M.; Griffin, Darrin
ABSTRACT: Addressing student public speaking anxiety (PSA) through an introductory speaking course is a fundamental pedagogical touchpoint. The current study replicates and extends PSA research by seeking to understand the nature of change in PSA that students experience. Results indicate that students' fears and anxieties regarding public speaking change before the first speech (Time 1) and after the last speech (Time 2) in the course such that almost half who reported the same fears at Time 1 and Time 2 indicated that the fear had decreased or diminished in intensity. Memory glitches were the most often cited fear at both Time 1 and Time 2. Confirming previous research, student PSA decreased over time. These findings extend previous investigations by highlighting the intensity of change experienced about specific fears identified and establishing a connection between fears and PSA. Training students in an introductory speaking course appears effective (and economical) in reducing levels of PSA. Future research should target the link between specific pedagogical tools and changes in student PSA.